Pengambilan Harta Wakaf Perpektif Hukum Islam dan Undang-Undang No. 41 Tahun 2004 (Studi Kasus di Desa Karang Anyar Kec. Jati Agung Kab. Lam-Sel Tahun 2016) - Ahmad Mukhlishin; Teguh Arifin; Muhammad Dimyati (Ajudikasi : Jurnal Ilmu Hukum, 2018)
According to Islamic Law, Wakaf is to give up land or other objects that can be utilized by the Islamic Ummah without damaging the Wakaf objects and to grant the Wakaf objects to someone or to a legal entity to be utilized for the benefit of Islamic Ummah. Based on Agrarian Law, wakaf is an eternal transfer of right. The consequence is that the land becomes institutionalized forever and the right to land can no longer be transfered to the other partie either by means of trading, exchanging, granting and so on unless there is a legal reason allowing it.his analytical descriptive study with sociological juridical approach described the fact found in the community of Percut Jati Agung subdistrict. The result of this study showed that the problematic of wakaf land registrationin in karang anyar Percut jati agung  subdistrict, lampung selatan District were 1) the community members living in Percut jati agung Subdistrict did not understand much especially about wakaf land registration and certification, 2) the wakif (the one donates the wakaf object) could not issue the certificate for the donated land, while the declaration of wakaf (donation) had been made at KUA by PPAIW, and 3) the personnel working of KUA or BPN was very minimal that many declarations of donated land at KUA or Registrations of the donated land at BPN have not been handled. In the process of donated land registration.The related parties are suggested to handle the wakaf cases more maximally and to socialize the land registration and land donation that it can create a legal awareness in the community members and they understand the importance of land registration